2012
DOI: 10.1002/14651858.cd008250.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Breathing exercises for chronic obstructive pulmonary disease

Abstract: Analysis 2.4. Comparison 2 Diaphragmatic breathing versus no breathing retraining, Outcome 4 Diaphragmatic mobility. Analysis 2.5. Comparison 2 Diaphragmatic breathing versus no breathing retraining, Outcome 5 Ratio of rib cage to abdominal motion during normal breathing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
1
10

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(154 citation statements)
references
References 55 publications
4
139
1
10
Order By: Relevance
“…However, in a meta-analysis by HOLLAND et al [74] it was concluded that breathing exercises improve functional exercise capacity in patients with COPD compared to no intervention despite the fact that there are no consistent effects on dyspnoea or health-related quality of life. Breathing exercises may be useful to improve exercise tolerance in selected individuals with COPD who are unable to undertake exercise training [74].…”
Section: Breathing Retraining (Or Breathing Exercises)mentioning
confidence: 99%
“…However, in a meta-analysis by HOLLAND et al [74] it was concluded that breathing exercises improve functional exercise capacity in patients with COPD compared to no intervention despite the fact that there are no consistent effects on dyspnoea or health-related quality of life. Breathing exercises may be useful to improve exercise tolerance in selected individuals with COPD who are unable to undertake exercise training [74].…”
Section: Breathing Retraining (Or Breathing Exercises)mentioning
confidence: 99%
“…In asthma, breathing retraining typically aims to eliminate over-breathing by developing a slow, shallow, controlled breathing pattern. The breathing strategies used in COPD, such as pursed lip breathing and diaphragmatic breathing [32], have not been tested in people with asthma and should not be routinely offered to this patient group.…”
Section: Asthmamentioning
confidence: 99%
“…Since pursed-lip breathing (PLB) is one of the most favored breathing techniques in patients with COPD [25], it remains unknown whether patients with IPF would also benefit from PLB. Although most studies that provided breathing retraining to IPF patients also used the PLB technique, the respiratory pathophysiologies of COPD and IPF are very different.…”
Section: Education and Breathing Retrainingmentioning
confidence: 99%